Direct C–H trifluoromethylation of di- and trisubstituted alkenes by photoredox catalysis - Tomita, Ren; Yasu, Yusuke; Koike, Takashi; Akita, Munetaka (Beilstein Journal of Organic Chemistry, 2014)
Background: Trifluoromethylated alkene scaffolds are known as useful structural motifs in pharmaceuticals and agrochemicals as well as functional organic materials. But reported synthetic methods usually require multiple synthetic steps and/or exhibit limitation with respect to access to tri- and tetrasubstituted CF3-alkenes. Thus development of new methodologies for facile construction of Calkenyl–CF3 bonds is highly demanded.Results: The photoredox reaction of alkenes with 5-(trifluoromethyl)dibenzo[b,d]thiophenium tetrafluoroborate, Umemoto’s reagent, as a CF3 source in the presence of [Ru(bpy)3]2+ catalyst (bpy = 2,2’-bipyridine) under visible light irradiation without any additive afforded CF3-substituted alkenes via direct Calkenyl–H trifluoromethylation. 1,1-Di- and trisubstituted alkenes were applicable to this photocatalytic system, providing the corresponding multisubstituted CF3-alkenes. In addition, use of an excess amount of the CF3 source induced double C–H trifluoromethylation to afford geminal bis(trifluoromethyl)alkenes.Conclusion: A range of multisubstituted CF3-alkenes are easily accessible by photoredox-catalyzed direct C–H trifluoromethylation of alkenes under mild reaction conditions. In particular, trifluoromethylation of triphenylethene derivatives, from which synthetically valuable tetrasubstituted CF3-alkenes are obtained, have never been reported so far. Remarkably, the present facile and straightforward protocol is extended to double trifluoromethylation of alkenes.
Keywords: electrophilic trifluoromethylating reagent; multi-substituted alkene; photoredox catalysis; radical reaction; trifluoromethylation